Recommendations for management of diabetes during Ramadan: update 2020, applying the principles of the ADA/EASD consensus. Issue 1 (4th May 2020) - Ibrahim, Mahmoud; Davies, Melanie J; Ahmad, Ehtasham; Annabi, Firas A; Eckel, Robert H; Ba-Essa, Ebtesam M; El Sayed, Nuha Ali; Hess Fischl, Amy; Houeiss, Pamela; Iraqi, Hinde; Khochtali, Ines; Khunti, Kamlesh; et al.
Abstract : Fasting the Holy month of Ramadan constitutes one of the five pillars of the Muslim faith. Although there is some evidence that intermittent fasting during Ramadan may be of benefit in losing weight and cardiometabolic risk factors, there is no strong evidence these benefits apply to people with diabetes. The American Diabetes Association/European Association for the Study of Diabetes consensus recommendations emphasize the importance of patient factors and comorbidities when choosing diabetes medications including the presence of comorbidities, atherosclerotic cardiovascular disease, heart failure, chronic kidney disease, hypoglycemia risk, weight issues and costs. Structured education and pre-Ramadan counseing are key components to successful management of patients with diabetes. These should cover important aspects like glycemic targets, self-monitoring of blood glucose, diet, physical activity including Taraweeh prayers, medication and dose adjustment, side effects and when to break the fast. The decision cycle adapted for the specific situation of Ramadan provides an aid for such an assessment. Children with type 1 diabetes should strongly be advised not to fast due to the high risk of acute complications such as hypoglycemia and probably diabetic ketoacidosis (DKA), although there is very little evidence that DKA is increased in Ramadan. Pregnant women with diabetes or gestational diabetes should be advised to avoid fasting because of possible negative maternal and fetal outcomes. Hypoglycemia is a common concern during Ramadan fasting. To prevent hypoglycemic and hyperglycemic events, we recommend the adoption of diabetes self-management education and support principles. The use of the emerging technology and continuous glucose monitoring during Ramadan could help to recognize hypoglycemic and hyperglycemic complications related to omission and/or medication adjustment during fasting; however, the cost represents a significant barrier.